Ice model tests with a cylindrical structure to investigate dynamic ice-structure interaction - Onken, G.; Evers, Karl-Ulrich; Haase, Andrea; Jochmann, Peter (Curran, 2014)
A physical analogous model of the lighthouse Norstrømsgrund has been built and tested in a series of model tests in ice at HSVA. The dynamic behavior of the lighthouse is simplified as a SDOF-system (single degree of freedom) by translational displacement in the ice plane, which is found to be justified by full scale data. The model's natural frequency and stiffness are adjustable by correct choice of springs and additional mass. Several tests have proven the accuracy of adjustability. Stiffness as well as mass is subject to physical constraints, e.g. a minimum mass which can not be fallen short of and a maximum feasible stiffness. Due to these limitations, the model's stiffness had to be reduced. A reasonable approach to convert measured accelerations from model tests to the less compliant full scale structure has been found and used for the model test results. Several events of ice-induced vibrations have been observed. Measured forces and accelerations during dynamic ice-structure interaction at model scale are in good agreement with full scale measurements. The test set-up is suitable to provide realistic results on the dynamic behavior of cylindrical offshore structures. The paper describes the design of the test set-up, instrumentation and calibration, performance and analysis of conducted tests, and general findings.